OPTIMASI ALOKASI AIR PADA SISTEM IRIGASI KOMERING DALAM USAHA PENINGKATAN PRODUKSI PANGAN DAN PENDAPATAN PETANI KABUPATEN OGAN KOMERING ULU TIMUR - , Muhammad Suro, SP ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Ogan Komering Ulu Eastern District with an area of 3370 km2 area has 76,888 ha of paddy fields and irrigation water that could land area of 45,904 ha. The main river is the River Komering. Along the river there are many settlements. At first the water source for DI. Komeringg taken from Komering River downstream through the decision-free (free intake) Lives cage was built in 1937 since the Dutch era. Over time, conditions and river morphology Komering undergone many changes that cause the function of the building free intake cage Lives experiencing problems due to high sedimentation so it does not ensure the continuity of provision of irrigation water. In 1990 a dam was built Perjaya so IN. Komering can be irrigated. In DI water needs. Komering not be met in the dry season the dam Perjaya. This is due to the availability of a little water so that the discharge is available is relatively small. To solve the above problems, it would require optimization of water allocation for irrigation Komering land potential in its service area and can be optimized to provide maximum benefits. This study airms to get the total value of the maximum profit by optimizing the alocation of irrigation water the use of debit and land mainstay in the field. The results are expected to provide and optimal solution acreage by type of commodity crops based on need and availability of water and can provide input to decision-makers rearding the management of water resources for Komering River Irrigation Area Komering. Optimization analysis performed using a linear program (Lindo version 6.1) which in terms of technical and ecomoic aspects based irrgation management polcy reform. The results showed that the optimum planting area and the maximum profit earned is determined by the availability of the allocated discharge. For the allocation of discharge mainstay of Q = 100% gives the optimum acreage of 122,922 ha or equal to 267.70% cropping intensity and the maximum profit of Rp 893,253,809,281.00. When allocation of discharge reduced by 50% then the optimum acreage acquired 612.88 hectares or equal to 213.77% cropping intensity and the maximum profit of Rp 834,228,764,040.00. Overall water balance still provide a surplus of 1.475.962.50 m3 per year for the allocation of debit mainstay for Q = 100% and 12.8174 million m3 for the allocation mainstay discharge Q = 50%, so that the water allocation policy for the DI. Komering can be implemented. The results of sensitivity analysis showed that changes in allocation parameters are more sensitive to discharge mainstay optimum planting area of rice compared with the kinds of commodity price changes in parameters of the production unit.